Stabilizing Alkaline Treatment Parameters for Enhancing Tensile Strength of Bamboo Fiber Composites - ABDUL RAHMAN, NURUL ATIQAH; HASHIM, MOHD YUSSNI (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Bamboo fibers are increasingly recognized for their sustainability and versatility in composite manufacturing, yet their inherent mechanical properties are insufficient for many industrial applications. This study aims to enhance the tensile strength of bamboo fiber composites through alkaline treatment, specifically focusing on the effects of sodium hydroxide (NaOH) treatment at concentrations of 2% and 10% for durations of 1 and 10 hours. The research employs tensile testing using a Universal Testing Machine (UTM) in accordance with ASTM D3039 standards to evaluate the treated and untreated composites. Results indicate significant improvements in tensile strength of the treated bamboo fiber composites. These findings confirm that stable alkaline treatment parameters enhances the mechanical properties which is tensile strength, making bamboo fiber composites more viable for high-performance industrial applications.